Layer-specific changes of KCC2 and NKCC1 in the mouse dentate gyrus after entorhinal denervation - Del Turco, Domenico; Paul, Mandy H.; Schlaudraff, Jessica; Muellerleile, Julia; Bozic, Fran; Vuksic, Mario; Jedlicka, Peter; Deller, Thomas (Frontiers in Molecular Neuroscience, 2023)
The cation-chloride cotransporters KCC2 and NKCC1 regulate the intracellular Cl- concentration and cell volume of neurons and/or glia. The Cl- extruder KCC2 is expressed at higher levels than the Cl- transporter NKCC1 in mature compared to immature neurons, accounting for the developmental shift from high to low Cl- concentration and from depolarizing to hyperpolarizing currents through GABA-A receptors. Previous studies have shown that KCC2 expression is downregulated following central nervous system injury, returning neurons to a more excitable state, which can be pathological or adaptive. Here, we show that deafferentation of the dendritic segments of granule cells in the outer (oml) and middle (mml) molecular layer of the dentate gyrus via entorhinal denervation in vivo leads to cell-type- and layer-specific changes in the expression of KCC2 and NKCC1. Microarray analysis validated by reverse transcription-quantitative polymerase chain reaction revealed a significant decrease in Kcc2 mRNA in the granule cell layer 7 days post-lesion. In contrast, Nkcc1 mRNA was upregulated in the oml/mml at this time point. Immunostaining revealed a selective reduction in KCC2 protein expression in the denervated dendrites of granule cells and an increase in NKCC1 expression in reactive astrocytes in the oml/mml. The NKCC1 upregulation is likely related to the increased activity of astrocytes and/or microglia in the deafferented region, while the transient KCC2 downregulation in granule cells may be associated with denervation-induced spine loss, potentially also serving a homeostatic role via boosting GABAergic depolarization. Furthermore, the delayed KCC2 recovery might be involved in the subsequent compensatory spinogenesis.